2021
DOI: 10.1126/sciadv.abg3013
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72-derived arginine-containing dipeptide repeats associate with axonal transport machinery and impede microtubule-based motility

Abstract: A hexanucleotide repeat expansion in the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). How this mutation leads to these neurodegenerative diseases remains unclear. Here, we show using patient stem cell–derived motor neurons that the repeat expansion impairs microtubule-based transport, a process critical for neuronal survival. Cargo transport defects are recapitulated by treating neurons from healthy individuals with proline-arginine and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…Irrespective of the precise mechanisms, the targets for pathogenic C9orf72 expansion-mediated toxicity are not properly understood. Damage to mitochondria, the ER, autophagy, intracellular transport processes including axonal transport and nucleocytoplasmic trafficking, and Ca 2+ signaling have all been linked to mutant C9orf72 Braems et al, 2020;Cook & Petrucelli, 2019;Dafinca et al, 2016Dafinca et al, , 2020Fumagalli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the precise mechanisms, the targets for pathogenic C9orf72 expansion-mediated toxicity are not properly understood. Damage to mitochondria, the ER, autophagy, intracellular transport processes including axonal transport and nucleocytoplasmic trafficking, and Ca 2+ signaling have all been linked to mutant C9orf72 Braems et al, 2020;Cook & Petrucelli, 2019;Dafinca et al, 2016Dafinca et al, , 2020Fumagalli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from variations in the repeat number among individuals, there is variation in repeat size in the same individual when compared between CNS and blood(Van Mossevelde et al, 2017 ). Although the actual function of the C9orf72 encoded protein is not known, the pathogenic repeat expansion in C9orf72 causes haploinsufficiency as well as a gain of function in the form of aggregating expanded RNAs and dipeptide repeat proteins (Balendra and Isaacs, 2018 ; Fumagalli et al, 2021 ).…”
Section: Common Mechanisms Of Neurodegeneration In Als and Ftdmentioning
confidence: 99%
“…This is in line with Abo-Rady et al (2020) who reported that lysosome trafficking is also impaired in neurons with the C9orf72 repeat expansion. Moreover, Fumagalli et al (2021) also showed that when control iPSC-derived motor neurons and Drosophila neurons were exposed to poly-PR and poly-GR, comparable effects in microtubule transport deficits were found. Protein interaction studies performed in MNs and post-mortem patient tissues revealed an association of arginine-rich DPRs with kinesin-1, dynein, and, microtubules.…”
Section: Axonal Transport Degeneration In C9orf72mentioning
confidence: 91%
“…Recently, Fumagalli et al (2021) demonstrated the existence of inhibitory interactions of arginine-rich DPRs with axonal transport machinery in C9orf72-associated ALS/FTD. In this study, the authors observed impaired microtubule-based transport in iPSC-derived MNs from C9orf72-ALS/FTD patients, including elevated stalled cargoes.…”
Section: Axonal Transport Degeneration In C9orf72mentioning
confidence: 99%